(untitled) (Philosophy and Progress, 2024)
The purpose of this study is to depict human values in Buddhist philosophy. This research is completed in three steps: 1. to present a brief overview on basic human values, 2. to present a brief overview on human values in Buddhist philosophy, 3. the need for human values in today’s society. Buddhist philosophy is a philosophy of human essence. This philosophy teaches people the true human values necessary to become complete human beings. That if held, human life can be shaped and inspired by true human values. And human values are the first condition for building order and just society. Human values refer to relatively stable beliefs composed of a number of attitudes. Human values are the thoughts, goals and objectives that govern and guide human behavior, practices and activities. Fairness, honesty and decency serve as the foundation of human values. Respecting elders, serving others, good manners, tolerance, fairness, honesty etc. are examples of human values. Human values accelerate the mental development of the individual. And by thus developing personality it paves the way for good governance and puts an end to social decay. A child acquires values from family, school, community, playmates, society and traditions. These rules are also the main criteria for the formation of human values. Basically the things that deserve to be human characteristics and qualities are human values. As a result of nurturing these human values, ideological, religious or sacred issues are awakened over time. Through the concept of emotional and ideological unity, human values emerge psychologically in a person, which order and improve the state, society and family. And in this world, the teaching of Buddhist philosophy has strengthened human values among mankind. Therefore, the purpose of this paper is to present basic human values and human values in Buddhist philosophy, the need for human values in today’s society as well. Philosophy and Progress, Vol#73-74; No#1-2; Jan-Dec 2023 P 131-149